The Impact of Technology on Skill Development in India: Prospects and Challenges - Priya S.; Subidita Pattanaik; Dilip Kumar Bagal (Revista Electronica de Veterinaria, 2024)
India’s large and young population presents a significant opportunity for socio-economic progress and prosperity, but only if this human capital is gainfully skilled. Skill development has emerged as a crucial imperative for India’s sustainable growth and development. Technology has opened up new avenues for learning, making it more accessible, flexible, and work-integrated. It has also enhanced the quality and relevance of skill development by facilitating personalized feedback, benchmarking with global standards, and regularly updating course content. This article examines the prospects and challenges of technology-enabled skill development in India, exploring the opportunities and limitations of technology in transforming skill development. The article concludes that while technology has immense potential to revolutionize skill development, a coordinated effort among stakeholders is required to ensure that technology-enabled skill development is inclusive, equitable, and addresses the skill gaps in the labour market.